Identifikasi Isu Kepadatan Penduduk dan Strategi Penanganan di Apartment Transit Ujung Berung - Agustian Rahayu; Jasmine Zahra Fernando; Keysha R. Aisy (GLOBAL SCIENTS PUBLISHER, 2026)
The rapid population growth and urbanization in Bandung City have increased the demand for adequate and affordable housing, while the availability of land continues to decline. To address this issue, the government has developed vertical housing such as the Ujung Berung Transit Apartment as a temporary residence for low-income communities. However, the high occupancy rate has led to population density issues that affect housing quality, limited space, and reduced living comfort. This study aims to identify the factors causing population density in the Ujung Berung Transit Apartment and formulate strategies for effective management. The research employs a descriptive qualitative approach through field observations, interviews with residents and management, and analysis of social and physical conditions. The findings indicate that the main causes of density include high resident mobility, limited maintenance budgets, and uncoordinated socio-economic diversity among occupants. The proposed strategies involve improving residential management systems, implementing socio-economic empowerment programs, optimizing communal facilities, and providing ongoing supervision from the government and housing authorities to create a healthy, orderly, and sustainable living environment. These findings are expected to serve as a reference for developing more effective models of vertical housing management in densely populated urban areas.